2015
DOI: 10.1099/ijsem.0.000634
|View full text |Cite
|
Sign up to set email alerts
|

Description of Diutina gen. nov., Diutina siamensis, f.a. sp. nov., and reassignment of Candida catenulata, Candida mesorugosa, Candida neorugosa, Candida pseudorugosa, Candida ranongensis, Candida rugosa and Candida scorzettiae to the genus Diutina

Abstract: Three strains (DMKU-RE28, DMKU-RE43T and DMKU-RE123) of a novel anamorphic yeast species were isolated from rice leaf tissue collected in Thailand. DNA sequence analysis demonstrated that the species forms a sister pair with Candida ranongensis CBS 10861T but differs by 24-30 substitutions in the LSU rRNA gene D1/D2 domains and 30-35 substitutions in the ITS region. A phylogenetic analysis based on both the small and the large rRNA gene subunits confirmed this connection and demonstrated the presence of a clad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…catenulata type sequence over 385 bases [ 42 ]. Phylogenetic analysis by Khunnamwong et al [ 18 ] suggested that D . catenulata lies in an unaffiliated clade within the Saccharomycetales, and is possibly related to the Debaryomycetaceae/Metschnikowiaceae.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…catenulata type sequence over 385 bases [ 42 ]. Phylogenetic analysis by Khunnamwong et al [ 18 ] suggested that D . catenulata lies in an unaffiliated clade within the Saccharomycetales, and is possibly related to the Debaryomycetaceae/Metschnikowiaceae.…”
Section: Resultsmentioning
confidence: 99%
“…Additional species were added to the clade following the identification of Candida ranongenesis from estuarine water, and Candida mesorugosa , Candida neorugosa and Candida pseudorugosa from clinical samples [ 16 , 17 ]. Khunnamwong et al [ 18 ] carried out a detailed phylogenetic analysis of the clade following the identification of three other related endophytic yeasts from rice tissue. Using ribosomal DNA sequencing, they confirmed that all these species are members of the Saccharomycetales, but again, were unable to completely determine the phylogenetic position.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…D. siamensis, and epiphytic yeast species such as Hannaella siamensis, H. phetchabunensis, H. pagnoccae, Nakazawaea siamensis, Pseudozyma vetiver and Wickerhamomyces siamensis (Chamnanpa et al, 2013;Kaewwichian et al, 2013a, 20142015;Landell et al, 2014). Some species were described based on the strains isolated from the phylloplane and inner tissue of plant leaves such as O. tropicalis, Papiliotrema siamense and Wickerhamomyces siamensis (Surussawadee et al, 2014;Khunnamwong et al, 2014Khunnamwong et al, , 2015a. This information indicates that plant leaves are one of the important habitats of yeast species.…”
Section: Species Delineation and Phylogenetic Placementmentioning
confidence: 99%
“…Endophytic yeasts that have been found in plant leaves include both ascomycetous yeasts such as Candida guilliermondii, Candida oleophila, Candida railenensis, Cyberlindnera saturnus, Diutina siamensis, Metschnikowia pulcherrima, Wickerhamomyces anomalus and Wickerhamiella siamensis (Nassar et al, 2005;Isaeva et al, 2010;Rodríguez et al, 2011;Oliveira et al, 2012;Khunnamwong et al, 2014Khunnamwong et al, , 2015a (Gai et al, 2009;Abdel-Motaal et al, 2009;Isaeva et al, 2010;Khan et al, 2012;Akhtyamova & Sattarova, 2013;Khunnamwong et al, 2015b;Solis et al, 2015).…”
mentioning
confidence: 99%